Hyaluronic acid purification method based on self-microporous sulfonated polyether sulfone composite membrane and application thereof in hair dye preparation

CN122917211APending Publication Date: 2026-10-16ZHEJIANG UNIV OF TECH +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611424697.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-15
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0008]本发明的目的是克服现有技术的不足,克服传统商业超滤膜耐污染性不良的情况,提供了一种基于自具微孔磺化聚醚砜复合膜的透明质酸纯化方法及其在染发剂制备中的应用

Benefits of technology

本发明通过限定条件得到自具微孔磺化聚醚砜复合膜,组装在膜评价仪中,对透明质酸进行纯化处理,充分利用该自具微孔磺化聚醚砜复合膜在溶液中易分散、不团聚,其刚性的骨架结构和空间的扭曲,具有丰富的永久性微孔和大比表面积,而且聚合物的孔径和比表面积可调控,共价键结构赋予了材料优异的稳定性,季铵化的自聚微孔聚合物与磺化的聚醚砜聚合酸碱对作用,实现了两种聚合物在分子层面的静电自组装,提高了共混超滤膜优异的性能:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122917211A_ABST
    Figure CN122917211A_ABST
Patent Text Reader

Abstract

The application discloses a hyaluronic acid purification method based on self-microporous sulfonated polyether sulfone composite membranes and application of the hyaluronic acid purification method in preparation of hair dyes, and the purification method is as follows: self-microporous sulfonated polyether sulfone composite membranes are assembled in a membrane cell of a membrane evaluation instrument, and a cross-flow water inlet and outlet mode is used to purify a hyaluronic acid aqueous solution to be treated, the self-microporous sulfonated polyether sulfone composite membranes comprise a non-woven fabric substrate and a functional separation layer coated on the non-woven fabric substrate, and the functional separation layer is formed by blending of a quaternized self-microporous polymer and sulfonated polyether sulfone through acid-base pair electrostatic self-assembly. According to the purification method, the self-microporous sulfonated polyether sulfone composite membranes have rich amino groups, and nitrogen-containing groups endow the self-microporous sulfonated polyether sulfone composite membranes with resistance to protein pollution, and the protein removal rate is stably above 99.5%, the hair dyes prepared from the hyaluronic acid purified through the purification treatment are uniform in dyeing, have remarkable hair care and color protection effects, hair is still smooth and moisturized after 20 times of washing, and glossiness does not obviously decrease.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of separation and purification technology, specifically relating to a method for purifying hyaluronic acid using a microporous sulfonated polyethersulfone composite membrane on a membrane evaluation instrument, and the application of the purified hyaluronic acid in the preparation of hair dye. Background Technology

[0002] Hyaluronic acid (HA), also known as hyaluronic acid, is a macromolecular viscous polysaccharide composed of repeating disaccharide units, D-glucuronic acid and N-acetylglucosamine, linked by alternating β(1-3) and β(1-4) glycosidic bonds. It was first extracted from bovine vitreous eyes by Meyer et al. in 1934. Hyaluronic acid or its sodium salt, sodium hyaluronate, possesses excellent moisturizing, anti-aging, repairing, and lubricating properties, and is therefore widely used in the fields of beauty, medicine, and health care. In recent years, it has been explored as an additive in hair dye formulations (e.g., CN 103169635, CN113143801, CN 117427020, etc.). Results show that adding sodium hyaluronate to hair dyes not only reduces scalp irritation but also nourishes the hair, making it more moisturized and shiny. Given the wide application of hyaluronic acid in the aforementioned fields, researchers are increasingly concerned about how to obtain higher purity hyaluronic acid to reduce the impact of impurities on the human body. The main sources of hyaluronic acid are rooster comb extraction and microbial fermentation. Regardless of whether the extraction method is tissue extraction or fermentation, the crude hyaluronic acid extracted contains some proteins, nucleic acids, and other impurities, requiring rigorous purification and separation processes to meet the corresponding usage standards.

[0003] Currently, hyaluronic acid purification methods mainly rely on organic solvent precipitation, ion exchange chromatography, and enzymatic hydrolysis. However, organic solvent precipitation methods suffer from problems such as high solvent consumption, difficult recovery, severe environmental pollution, and high production costs. For example, the methods for purifying hyaluronic acid disclosed in patents such as US4517295, US4780414, US5563051, and US2006012987 use large amounts of organic solvents to precipitate impurities. Although chromatography provides high purity, it has a small processing capacity and long cycle time, making it difficult to meet the needs of large-scale industrial production.

[0004] Ultrafiltration uses a membrane with a suitable molecular weight cutoff value to separate components in crude hyaluronic acid based on their different molecular weights. This process concentrates the polysaccharides present in the ultrafiltration membrane retentate and removes small molecule impurities, making it suitable for large-scale production.

[0005] Polyethersulfone (PES) is one of the most widely used ultrafiltration membrane materials due to its excellent mechanical strength, heat resistance and chemical stability. However, traditional PES ultrafiltration membranes are not effective in removing proteins and membrane fouling occurs as purification progresses, which limits their application in the purification of hyaluronic acid.

[0006] In recent years, polymers with self-contained micropores (PIMs) have shown great potential in membrane separation due to their permanent microporous channels formed by rigid, twisted structures and high specific surface areas. However, when PIMs are directly blended with PES to prepare ultrafiltration membranes, the high rigidity and poor solubility of PIM molecular chains, coupled with their extremely poor thermodynamic compatibility with the PES matrix, easily lead to macroscopic or microscopic phase separation, resulting in unstable membrane performance and poor reproducibility. Furthermore, in the conventional non-solvent-induced phase inversion (NIPS) membrane formation process, the rapid mass transfer in the coagulation bath often destroys the microporous structure of PIMs, causing them to lose their original separation performance.

[0007] Therefore, it is particularly important to study an ultrafiltration membrane that can protect the integrity of the PIM microporous structure, achieve intrinsic antifouling function on the membrane surface and inside, precisely control the charge characteristics of the membrane to match the purification requirements of hyaluronic acid, effectively remove proteins from hyaluronic acid, and has strong antifouling resistance. Summary of the Invention

[0008] The purpose of this invention is to overcome the shortcomings of the prior art and the poor fouling resistance of traditional commercial ultrafiltration membranes, and to provide a method for purifying hyaluronic acid based on a microporous sulfonated polyethersulfone composite membrane and its application in the preparation of hair dyes.

[0009] This invention defines a method for purifying hyaluronic acid based on a self-porous sulfonated polyethersulfone composite membrane. The self-porous sulfonated polyethersulfone composite membrane is assembled in the membrane tank of a membrane evaluation instrument. Under specific conditions, a cross-flow inlet and outlet water method is used to purify the aqueous solution of hyaluronic acid to be treated. The self-porous sulfonated polyethersulfone composite membrane includes a non-woven fabric substrate and a functional separation layer coated thereon. The functional separation layer is formed by blending quaternized self-porous polymer and sulfonated polyethersulfone through electrostatic self-assembly via acid-base interaction.

[0010] Furthermore, the present invention specifies the purification conditions as follows: the flow rate of the hyaluronic acid aqueous solution is 30 L / min, the temperature is 30°C, and the operating pressure is 3 bar.

[0011] Furthermore, the present invention defines a method for preparing a microporous sulfonated polyethersulfone composite membrane, comprising the following steps: 1) Using tetraaminophenylporphyrin and dimethoxymethane (DMM) as monomers, a self-contained microporous polymer was obtained by trifluoromethanesulfonic acid (TFA) catalysis, and then quaternized with iodomethane to obtain a quaternized self-contained microporous polymer. 2) Disperse the quaternized microporous polymer and sulfonated polyethersulfone obtained in step 1) into a polar solvent, stir evenly, and let stand to degas to obtain the casting solution. 3) Apply the casting solution from step 2) onto the nonwoven fabric substrate, scrape it to the set thickness, and then transfer it to deionized water. Let it stand for 3 to 6 hours to complete solvent replacement and obtain a quaternized microporous polymer sulfonated polyethersulfone blend ultrafiltration membrane, which is a microporous sulfonated polyethersulfone composite membrane.

[0012] Furthermore, the present invention specifies the preparation process of the quaternized self-porous polymer in step 1) as follows: At room temperature and pressure, two monomers, tetraaminophenylporphyrin and dimethoxymethane, are placed in a reaction apparatus. Trifluoromethanesulfonic acid is added under a nitrogen atmosphere, and the reaction is catalytically carried out at 25°C to obtain the self-porous polymer. After the reaction is completed, iodomethane is added under heat and a quaternization reaction is carried out at 25°C. The reaction solution is washed and filtered, then dried in a vacuum oven to obtain the quaternized self-porous polymer. The synthetic route is as follows:

[0013] Furthermore, the present invention specifies that the molar ratio of tetraaminophenylporphyrin to dimethoxymethane in step 1) is 1:2-1:30, and the quaternization reaction time is 4h.

[0014] Furthermore, the present invention specifies that the polar solvent in step 2) is one of N,N-dimethylformamide, N,N-dimethylacetamide, or N-methylpyrrolidone; in the casting solution, the total mass concentration of the quaternized self-porous polymer and sulfonated polyethersulfone is 15%-20%, and the quaternized self-porous polymer accounts for 1.5% to 8.0% of the solid content of the casting solution.

[0015] Furthermore, the present invention specifies the preparation method of sulfonated polyethersulfone in step 2) as follows: after mixing polyethersulfone and concentrated sulfuric acid, sulfonate the mixture at 85 °C for 12 h to obtain a sulfonated polyethersulfone solution. Then, slowly add the sulfonated polyethersulfone solution dropwise into deionized water to precipitate the precipitate. Wash thoroughly with deionized water until the pH of the water is 6-7. The degree of sulfonation of the sulfonated polyethersulfone is 25%-35%.

[0016] Furthermore, the present invention specifies that in step 3), the thickness of the coated membrane is adjusted to 200μm-400μm using a flatbed coating machine, and the resulting ultrafiltration membrane can retain solutes with a molecular weight of 2000~100000 Daltons.

[0017] Furthermore, the present invention specifies that the concentration of hyaluronic acid in the solution to be treated is 500 ppm, the concentration of impurities is 100 ppm-200 ppm, and the impurity removal rate after purification is over 99.5%.

[0018] Furthermore, the present invention also defines the application of hyaluronic acid purified by a defined purification method in the preparation of hair dyes.

[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention obtains a self-porous sulfonated polyethersulfone composite membrane under defined conditions, assembles it in a membrane evaluation instrument, and purifies hyaluronic acid. It fully utilizes the self-porous sulfonated polyethersulfone composite membrane's easy dispersibility and non-agglomeration in solution, its rigid framework structure and spatial distortion, abundant permanent micropores, and large specific surface area. Furthermore, the polymer's pore size and specific surface area are controllable, and the covalent bond structure endows the material with excellent stability. The quaternized self-polymerizing microporous polymer and the sulfonated polyethersulfone polymer interact with each other via an acid-base pair, achieving electrostatic self-assembly of the two polymers at the molecular level, thus improving the excellent performance of the blended ultrafiltration membrane. 1) As can be clearly seen from the data of the embodiments of the present invention, the water flux of the self-porous sulfonated polyethersulfone composite membrane prepared by the present invention is as high as 83-99 L / (m²). 2 ·h), compared to Example 6 (56.06 L / (m 2 The throughput was increased by 48%-77%; at the same time, the retention rate of hyaluronic acid remained at a high level of 97%-99%, which was significantly better than that of Example 6 (95.06%), achieving a synergistic improvement in high throughput and high selectivity, and has practical application value. 2) This invention fully utilizes the molecular-level compatibility of quaternized microporous polymers and sulfonated polyethersulfone, as well as the anti-protein adsorption properties of porphyrin rings. The resulting membrane exhibits a flux reduction rate of only 7.4%-8.5% during 20 consecutive days of hyaluronic acid purification, compared to a flux reduction rate of 25.8% in Example 6. The fouling resistance retention rate of this invention is more than 3 times that of the control example, significantly reducing the cleaning frequency and operating costs. 3) This invention uses non-woven fabric instead of traditional glass substrate as the support layer. Through a direct sulfonation process with concentrated sulfuric acid at 85°C, the degree of sulfonation of sulfonated polyethersulfone is precisely controlled within the range of 25%-35%, so that its charge density is perfectly matched with the quaternized quaternized self-porous polymer, maximizing the electrostatic self-assembly effect of acid-base pair and optimizing the microphase separation structure within the membrane. Furthermore, this invention uses a deionized water static solvent replacement method to form the film, avoiding the collapse and destruction of the permanent microporous channels of the quaternized self-porous polymer by the rapid intrusion of non-solvents, thus completely preserving the high free volume and mass transfer channels of the quaternized self-porous polymer. 4) This invention purifies hyaluronic acid under specific conditions using a cross-flow inlet and outlet water method and a self-porous sulfonated polyethersulfone composite membrane. Because the self-porous sulfonated polyethersulfone composite membrane is rich in amino groups, the nitrogen-containing groups in its structure endow it with resistance to protein contamination. Its protein removal rate is stable at over 99.5%, which effectively solves the problem of poor fouling resistance of traditional commercial ultrafiltration membranes and has practical application value. 5) This invention uses hyaluronic acid purified by a microporous sulfonated polyethersulfone composite membrane for the synthesis of hair dye agent 1. The experimental results show that the hair dye containing the purified hyaluronic acid component has a good dyeing effect, uniform dyeing, and significant hair care and color protection effect. After 20 washes, the hair is still smooth and moisturized, and the luster does not decrease significantly. It has better hair care, color protection and moisturizing effect than hyaluronic acid purified by traditional sulfonated polyethersulfone ultrafiltration membrane. Attached Figure Description

[0020] Figure 1 These are Fourier transform infrared spectra of the microporous polymers prepared in Example 1.

[0021] Figure 2 These are the XRD diffraction patterns of the microporous polymers obtained in Example 1.

[0022] Figure 3 This is an X-ray diffraction pattern of the microporous polymer powder obtained by vacuum oven drying and freeze drying in Example 1.

[0023] Figure 4 This is a scanning electron microscope image of the microporous sulfonated polyethersulfone composite membrane in Example 1. Detailed Implementation

[0024] To enhance understanding of the present invention, the invention will be further described in detail below with reference to the embodiments and accompanying drawings. These embodiments are only for explaining the invention and do not constitute a limitation on the scope of protection of the invention.

[0025] Self-polymerizing microporous polymers possess good thermal stability, but most are powder materials, and their insolubility makes reprocessing difficult. This invention employs a solvent phase transfer method, utilizing the significant difference in solubility of a solute in two solvents. The process involves replacing the solute with a better solvent in a less favorable solvent and solidifying the solute, thereby preparing a porous ultrafiltration membrane. Incorporating the conjugated microporous polymer into the solvent solves the problem of difficult polymer powder processing. The solidification also improves the membrane's hydrophilicity, thus increasing the membrane's water flux.

[0026] Example 1: The preparation method of self-porous sulfonated polyethersulfone composite membrane includes the following steps:

[0027] (1) Preparation of quaternized microporous polymers At room temperature and pressure, 0.2 mmol of tetraaminophenylporphyrin and 1.0 mmol of dimethoxymethane were placed in a reaction apparatus. Then, 0.024 mmol of trifluoromethanesulfonic acid was added under a nitrogen atmosphere. After reacting at 25°C for 36 h, iodomethane was added and the temperature was maintained at 25°C for quaternization for 4 h. After washing and filtration, the product was dried in a vacuum oven to obtain the quaternized microporous polymer, denoted as TP-ZK. (2) Preparation of microporous sulfonated polyethersulfone composite membrane: 0.1 g of quaternized self-porous polymer was dispersed in a 18% polyethersulfone-N-methylpyrrolidone solution with a sulfonation degree of 30%. The solution was stirred, allowed to stand to remove bubbles, and then the casting solution was poured onto a nonwoven fabric. The coating thickness was adjusted to 200 μm using a flatbed coater. After coating, the membrane was transferred to deionized water and allowed to stand overnight to completely replace the solvent, resulting in a quaternized self-porous polymer sulfonated polyethersulfone blend ultrafiltration membrane, which is the self-porous sulfonated polyethersulfone composite membrane.

[0028] The preparation process of the quaternized self-porous polymer of the present invention is the same as step 1), except that the feeding ratio of tetraaminophenylporphyrin and dimethoxymethane is changed. The molar ratio of tetraaminophenylporphyrin to dimethoxymethane is 1:2, 1:5, 1:10, and 1:30, respectively. The resulting quaternized self-porous polymers are TP-1:2, TP-1:5, TP-1:10, and TP-1:30, respectively. Their Fourier transform infrared spectra are shown below. Figure 1 As shown, the XRD pattern is as follows Figure 2 As shown.

[0029] The preparation process of the quaternized self-porous polymer of the present invention is the same as step 1), except that the final "vacuum oven drying" is replaced with "freeze drying". The obtained quaternized self-porous polymer is denoted as TP-LD. The X-ray diffraction patterns of the self-porous polymer powders TP-ZK and TP-LDX obtained by vacuum oven drying and freeze drying are shown below. Figure 3 As shown.

[0030] Figure 1 These are Fourier transform infrared spectra of the quaternized self-polymerizing microporous polymers with different feed ratios prepared in this embodiment. Figure 1 The chemical structure and functional group composition of the samples were systematically characterized by FTIR spectroscopy. All samples were analyzed at 3300–3500 cm⁻¹. -1 The regions all exhibit broad and gradual absorption, with no sharp -NH2 double peaks from the starting material tetraaminophenyl, indicating that the amino group fully participated in the polycondensation reaction and no free monomer residues; 3000 cm⁻¹ -1 sp appearing nearby 3 CH stretching vibration characteristic peak (2920 / 2850 cm⁻¹) -1This confirms that dimethoxymethane undergoes condensation polymerization with an amino group, successfully generating a methylene (-CH2-)-bridged structure; 1600–1500 cm⁻¹ -1 The strong C=C skeletal vibration peaks at 1450–1470 cm⁻¹ are fully preserved, demonstrating that the aromatic conjugated structure of the porphyrin / benzene ring was not destroyed by the acid-catalyzed reaction, thus preserving excellent catalytically active sites for the material; -1 The characteristic peak of CN stretching vibration at the location further confirms the successful construction of the three-dimensional cross-linked network structure and proves the successful synthesis of the quaternized self-polymerizing microporous polymer.

[0031] Figure 2 The XRD diffraction patterns of the microporous polymers prepared in Example 1 show that all four samples exhibit a broadened diffuse peak between 15° and 25°, indicating that they are mainly in an amorphous / weakly crystalline state with low crystallinity. The molecular chains of the amorphous polymers are relatively disordered, and the internal pores are usually mainly mesoporous / microporous.

[0032] Figure 3 This is the X-ray diffraction pattern of the quaternized microporous polymer prepared in this embodiment, from... Figure 3 The results show that comparing the XRD patterns of samples obtained by freeze-drying (TP-LD) and vacuum drying (TP-ZK) reveals that neither curve exhibits sharp diffraction peaks, but rather broadened diffuse characteristic peaks within the 10°-25° range. This indicates that the products obtained by both drying methods are predominantly amorphous, lacking a long-range ordered crystalline framework, consistent with the typical structural characteristics of porphyrin-based organic porous polymers. In the low-angle region, the freeze-dried sample shows a significant enhanced scattering signal, reflecting a relatively abundant mesoporous structure and a certain degree of short-range ordered stacking within the material. Conversely, the low-angle scattering signal of the vacuum-dried sample is significantly weakened, indicating that during solvent evaporation, capillary forces cause significant shrinkage and partial collapse of the pore structure, resulting in a decrease in pore order.

[0033] Figure 4 This is a scanning electron microscope (SEM) image of the microporous sulfonated polyethersulfone composite membrane prepared in this embodiment. Figure 4 The scanning electron microscope images show that the nonwoven fabric substrate has an intact structure, a smooth and dense surface without cracks or peeling, indicating that it is tightly bonded to the substrate and has excellent pore structure and interface condition.

[0034] In the following embodiments of the present invention, TP-1:5 from Example 1 is used as the raw material to prepare a microporous sulfonated polyethersulfone composite membrane.

[0035] Example 2: Preparation of self-porous sulfonated polyethersulfone composite membrane 0.1 g of the quaternized self-porous polymer (TP-1:5) prepared in Example 1 was dispersed in a 20% polyethersulfone-N,N-dimethylacetamide solution with a sulfonation degree of 25%. The solution was stirred, allowed to stand to remove bubbles, and then the casting solution was poured onto a nonwoven fabric. The film thickness was adjusted to 300 μm using a flatbed coater. After coating, the film was transferred to deionized water and allowed to stand overnight to completely replace the solvent. The concentration of the quaternized self-porous polymer and the sulfonated polyethersulfone casting solution in the casting solution was 20%, and the quaternized self-porous polymer accounted for 2.0% of the solid content of the casting solution.

[0036] Example 3: Preparation of self-porous sulfonated polyethersulfone composite membrane 0.2 g of the quaternized microporous polymer prepared in Example 1 was dispersed in a 20% polyethersulfone-N,N-dimethylformamide solution with a sulfonation degree of 35%. The solution was stirred, allowed to stand to remove bubbles, and then the casting solution was poured onto a nonwoven fabric. The film thickness was adjusted to 400 μm using a flatbed coater. After coating, the film was transferred to deionized water and allowed to stand overnight to completely replace the solvent. The concentration of the quaternized microporous polymer and the sulfonated polyethersulfone casting solution in the casting solution was 20%, and the quaternized microporous polymer accounted for 2.0% of the solid content of the casting solution.

[0037] Example 4: Preparation of self-porous sulfonated polyethersulfone composite membrane 0.2 g of the quaternized microporous polymer prepared in Example 1 was dispersed in a polyethersulfone-N-methylpyrrolidone solution with a concentration of 18% and a sulfonation degree of 30%. The solution was stirred, allowed to stand to remove bubbles, and then the casting solution was poured onto a nonwoven fabric. The film thickness was adjusted to 300 μm using a flatbed coater. After coating, the film was transferred to deionized water and allowed to stand overnight to completely replace the solvent. The concentration of the quaternized microporous polymer and the sulfonated polyethersulfone casting solution in the casting solution was 18%, and the quaternized microporous polymer accounted for 2.0% of the solid content of the casting solution.

[0038] Example 5: Preparation of a microporous sulfonated polyethersulfone composite membrane 0.3 g of the quaternized microporous polymer prepared in Example 1 was dispersed in a polyethersulfone-N-methylpyrrolidone solution with a concentration of 18% and a sulfonation degree of 30%. The solution was stirred, allowed to stand to remove bubbles, and then the casting solution was poured onto a nonwoven fabric. The film thickness was adjusted to 300 μm using a flatbed coater. After coating, the film was transferred to deionized water and allowed to stand overnight to completely replace the solvent. The concentration of the quaternized microporous polymer and the sulfonated polyethersulfone casting solution in the casting solution was 15%, and the quaternized microporous polymer accounted for 2.5% of the solid content of the casting solution.

[0039] Example 6: Preparation of a conventional sulfonated polyethersulfone ultrafiltration membrane (Comparative Example 1) Sulfonated polyethersulfone (SPES) powder with a sulfonation degree of 30% was placed in a vacuum drying oven and dried continuously at 60°C for 14 h. 13 g of the dried SPES powder and 50 mL of N-methylpyrrolidone (NMP) were added to a three-necked flask and ultrasonically stirred at 200 r / min for 40 min at 50°C. The mixture was then heated to reflux until the SPES powder was completely dissolved. 2 mL of polyethylene glycol 1000 (PEG1000) was added, and stirring and reflux were continued for 12 h. After standing for 30 h to remove bubbles, the prepared sol was coated onto a plate using a membrane fabrication device, left to stand for 40 s, and then immersed in water at 40°C for 12 h to obtain a SPES ultrafiltration membrane.

[0040] The microporous sulfonated polyethersulfone composite membranes prepared in Examples 1-5 and the sulfonated polyethersulfone (SPES) ultrafiltration membrane prepared in Example 6 of this invention are used to purify hyaluronic acid. The microporous sulfonated polyethersulfone composite membranes prepared in Examples 1-5 and the sulfonated polyethersulfone (SPES) ultrafiltration membrane prepared in Example 6 were cut into circular membrane sheets with a diameter of 5.7 cm and placed on a membrane evaluation instrument for ultrafiltration purification test of hyaluronic acid aqueous solution. The hyaluronic acid aqueous solution was 500 ppm hyaluronic acid aqueous solution, which was used as the feed liquid.

[0041] The test employed a cross-flow inlet / outlet water configuration with a flow rate of 30 L / min, a water temperature of 30℃, and an operating pressure of 3 bar. Inlet water samples, filtrate, and their volume were collected during the test to calculate the membrane's permeability performance. Absorption peaks at wavelengths of 195-220 nm were measured using a UV-Vis spectrophotometer to calculate the efficiency of hyaluronic acid retention.

[0042] The formula for calculating the permeability coefficient is as follows:

[0043] V For a osmotic system, L; A For the effective membrane area, (m 2 ); t The infiltration time is in hours (h). P The operating pressure is bar.

[0044] The formula for calculating the retention rate is as follows:

[0045] C p The concentration of the permeate is... C f This refers to the concentration of the feed liquid.

[0046] The results of hyaluronic acid purification in each embodiment are shown in Table 1.

[0047] Table 1. Hyaluronic acid purification results for each example.

[0048] As shown in the table above, compared with Example 6 (Comparative Example 1), the self-porous sulfonated polyethersulfone composite membranes obtained in Examples 1-5 exhibit higher water flux and retention efficiency for the purification of hyaluronic acid, with a water flux as high as 83-99 L / (m²). 2 ·h), compared to Example 6 (56.06 L / (m 2 The efficiency of hyaluronic acid retention is increased by 48%-77%; at the same time, the retention rate of hyaluronic acid remains at a high level of 97%-99%, which is significantly better than Example 6 (95.06%), and has practical application value.

[0049] Examples of the application of hyaluronic acid in hair dye Two-component hair dyes are currently the mainstream type of permanent hair dye. They generally consist of a dyeing agent (referred to as Agent 1) and an oxidizing agent (referred to as Agent 2). During the dyeing process, Agent 1 and Agent 2 are mixed in a 1:1 mass ratio before use. Hyaluronic acid is used in the formulation of Agent 1 of the hair dye. This invention provides examples of the application of hyaluronic acid in the preparation of hair dyes.

[0050] According to the feeding amounts listed in Table 2, Examples 7 and 8 both contain hyaluronic acid components with consistent content, while Example 9 does not contain hyaluronic acid components, but other components and their contents are consistent; the components of the two agents are also completely consistent; the difference lies in the following: Example 7 (hyaluronic acid purified by the self-porous sulfonated polyethersulfone composite membrane of Example 4 of this invention), Example 8 (control example 2, hyaluronic acid purified by the conventional sulfonated polyethersulfone ultrafiltration membrane of Example 6), and Example 9 (control example 3, without hyaluronic acid), agents 1 and 2 were prepared respectively, stirred and heated to 80℃-85℃, stirred at high speed for 10 min, and then stirred slowly and cooled to room temperature for later use. When using, first mix agents 1 and 2 evenly in a 1:1 ratio; apply the mixed hair dye evenly to the hair with a hair dye comb; after evenly applying the dye to the hair from top to bottom and inside to outside, leave it for 30 minutes, then rinse with warm water and blow-dry the hair.

[0051] Table 2 Hair dye components and their application effects

[0052] Following the table above,

[0053] As shown in Table 2, the hair dye in Example 7 has a good dyeing effect, with uniform dyeing and significant hair care and color protection effects. After 20 washes, the hair remains smooth and moisturized, and its shine does not decrease significantly. The hair dye in Example 8 (Comparative Example 2) also has a good dyeing effect, with uniform dyeing and significant hair care and color protection effects, but the hair shine begins to decrease after 16 washes. In contrast, Example 9 (Comparative Example 3) did not contain hyaluronic acid, resulting in roughness after dyeing. After 11 washes, the hair began to change color, and its shine decreased significantly. The comparative results of Examples 7, 8, and 9 show that hyaluronic acid has significant hair care and color protection effects, making the hair more moisturized and shiny. The comparison results of Examples 7 and 8 show that the hyaluronic acid purified using the technology of this invention has better hair care, color protection, and moisturizing effects than the hyaluronic acid purified by traditional sulfonated polyethersulfone ultrafiltration membrane.

[0054] As a further improvement, the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for purifying hyaluronic acid based on a microporous sulfonated polyethersulfone composite membrane, characterized in that... A self-porous sulfonated polyethersulfone composite membrane is assembled in the membrane tank of a membrane evaluation instrument. Under specific conditions, the hyaluronic acid aqueous solution to be treated is purified using a cross-flow inlet and outlet water method. The self-porous sulfonated polyethersulfone composite membrane includes a non-woven fabric substrate and a functional separation layer coated thereon. The functional separation layer is formed by blending quaternized self-porous polymer and sulfonated polyethersulfone through acid-base electrostatic self-assembly.

2. The method for purifying hyaluronic acid based on a microporous sulfonated polyethersulfone composite membrane according to claim 1, characterized in that... The purification conditions were: a flow rate of 30 L / min for the hyaluronic acid aqueous solution, a temperature of 30 °C, and an operating pressure of 3 bar.

3. The method for purifying hyaluronic acid based on a microporous sulfonated polyethersulfone composite membrane according to claim 1 or 2, characterized in that... The method for preparing a microporous sulfonated polyethersulfone composite membrane includes the following steps: 1) Using tetraaminophenylporphyrin and dimethoxymethane as monomers, a self-contained microporous polymer was obtained by catalysis with trifluoromethanesulfonic acid, and then quaternized with iodomethane to obtain a quaternized self-contained microporous polymer. 2) Disperse the quaternized microporous polymer and sulfonated polyethersulfone obtained in step 1) into a polar solvent, stir evenly, and let stand to degas to obtain the casting solution. 3) Apply the casting solution from step 2) onto the nonwoven fabric substrate, scrape it to the set thickness, and then transfer it to deionized water. Let it stand for 3 to 6 hours to complete solvent replacement and obtain a microporous sulfonated polyethersulfone composite membrane.

4. The method for purifying hyaluronic acid based on a microporous sulfonated polyethersulfone composite membrane according to claim 3, characterized in that... The preparation process of the quaternized self-porous polymer in step 1) is as follows: At room temperature and pressure, two monomers, tetraaminophenylporphyrin and dimethoxymethane, are placed in a reaction apparatus. Trifluoromethanesulfonic acid is added under a nitrogen atmosphere, and the reaction is catalyzed at 25°C to obtain the self-porous polymer. After the reaction is complete, iodomethane is added under heat to continue the quaternization reaction. The reaction solution is washed and filtered, then dried in a vacuum oven to obtain the quaternized self-porous polymer. The synthetic route is as follows: 。 5. The method for purifying hyaluronic acid based on a microporous sulfonated polyethersulfone composite membrane according to claim 3, characterized in that... In step 1), the molar ratio of tetraaminophenylporphyrin to dimethoxymethane is 1:2-1:30, and the quaternization reaction time is 4h.

6. The method for purifying hyaluronic acid based on a microporous sulfonated polyethersulfone composite membrane according to claim 3, characterized in that... The polar solvent in step 2) is one of N,N-dimethylformamide, N,N-dimethylacetamide or N-methylpyrrolidone; in the casting solution, the total mass concentration of the quaternized self-porous polymer and sulfonated polyethersulfone is 15%-20%, and the quaternized self-porous polymer accounts for 1.5% to 8.0% of the solid content of the casting solution.

7. The method for purifying hyaluronic acid based on a microporous sulfonated polyethersulfone composite membrane according to claim 3, characterized in that... The preparation method of sulfonated polyether sulfone in step 2) is as follows: after mixing polyether sulfone and concentrated sulfuric acid, sulfonate the mixture at 85 °C for 12 h to obtain a sulfonated polyether sulfone solution. Then, slowly add the sulfonated polyether sulfone solution to deionized water to precipitate the precipitate. Wash thoroughly with deionized water until the pH of the water is 6-7. The degree of sulfonation of the sulfonated polyether sulfone is 25%-35%.

8. The method for purifying hyaluronic acid based on a microporous sulfonated polyethersulfone composite membrane according to claim 1, characterized in that... In step 3), the thickness of the membrane is adjusted to 200μm-400μm using a flatbed coating machine. The resulting ultrafiltration membrane can retain solutes with a molecular weight of 2000~100000 Daltons.

9. The method for purifying hyaluronic acid based on a microporous sulfonated polyethersulfone composite membrane according to claim 1, characterized in that... The hyaluronic acid solution to be treated has a hyaluronic acid concentration of 500 ppm and an impurity concentration of 100 ppm-200 ppm. After purification, the impurity removal rate is over 99.5%.

10. The application of hyaluronic acid obtained by the purification method according to claim 1 in the preparation of hair dye.

Citation Information

Patent Citations

  • Methods and apparatus for generating and modulating illumination conditions

    US20060012987A9

  • Hyaluronic acid from bacterial culture

    US4517295A

  • Method of producing high molecular weight sodium hyallronate by fermentation of streptococcus

    US4780414A

  • Production of hyaluronic acid

    US5563051A